World Bank Group Support to Electricity Access, FY2000-2014 : An Independent Evaluation - Independent Evaluation Group (World Bank, Washington, DC, 2015)
The World Bank Group has committed to achieving universal access to electricity by 2030 under the Sustainable Energy for All (SE4All) initiative. This is a daunting challenge: more than 1 billion people do not have access, and another 1 billion have chronically inadequate or unreliable service. Most of those without access are poor, and the largest share is in Sub-Saharan Africa. Achieving universal access within 15 years for the low-access countries (those with under 50 percent coverage) requires a quantum leap from their present pace of 1.6 million connections per year to 14.6 million per year until 2030. The investment needed would be about $37 billion per year, including erasing generation deficits and meeting demand from economic growth. By comparison, in recent years, low-access countries received an average of $3.6 billion per year for their electricity sectors from public and private sources, including $1.5 billion per year from the World Bank Group. Development outcomes of the Bank Group’s assistance were generally favorable compared with other infrastructure sectors. However, performance in improving financial viability of country electricity sectors was below expectations. There were significant gaps in the Bank Group’s coverage of low-access countries, mostly in Sub-Saharan Africa. Median implementation time of World Bank investment projects was nine years, with time overruns attributable to inadequate project design and borrower capacity. Support for off-grid electrification was low and sporadic, with a few notable exceptions. The Bank Group’s growing non-conventional renewable energy portfolio is dealing with technology and regulatory challenges. Tracking welfare and gender impacts in World Bank projects has improved, and International Finance Corporation (IFC) has made a beginning in addressing these issues. The Bank made some significant pilot contributions to addressing the affordability of electricity connections. Collaboration grew among World Bank, IFC, and MIGA through joint projects, which helps break ground for the private sector in some high-risk and fragile countries, and supports a few large and complex projects. The scale of the SE4All challenge requires the Bank Group to reposition itself as a global solutions provider in the sector, going well beyond the confines of its own direct support for access. This evaluation points to the urgency for the Bank Group‘s energy practice to adopt a new and transformative strategy to help country clients orchestrate a national, sustained sector-level engagement for universal access. A major challenge in this effort is to deploy the Bank Group units’ individual and collective strengths beyond Bank Group–led projects and transactions to stimulate private sector investments for closing the financing gap, especially in generation, for low-access countries.